Measurement of intervention fidelity within paediatric rehabilitation for children with physical disabilities - Di, Rezze Briano (My University, 2012)
Intervention fidelity examines the degree to which an intervention is delivered as planned. Generic fidelity measures incorporate the active ingredients of more than one intervention and characteristics common to all interventions. Three studies were conducted to define the active ingredients of intervention for children with physical disabilities and generate a generic fidelity measure. These studies involved: (1) describing generic fidelity measures; (2) generating essential attributes of paediatric rehabilitation; and (3) differentiating between two interventions to consistently rate the behaviours of the therapist, child and parent.
(1) In a narrative review of generic fidelity measures, five measures were identified within the psychotherapy literature. These measures presented a variety of approaches to examine fidelity, described psychometric property standards, and highlighted 37 non-specific intervention items that were relevant to paediatric rehabilitation.
(2) A consensus process with eight experts and interviews with seventeen clinicians working with children with physical disabilities generated 35 attributes that highlighted the general observed therapist and client behaviours essential within a successful intervention session.
(3) The Paediatric Rehabilitation Observational measure of Fidelity (PROF) was developed (30 items) to evaluate specific and non-specific behaviours within two occupational therapy and physiotherapy interventions for children with cerebral palsy. Six trained raters examined 25 intervention videos for psychometric testing. Results indicated that the PROF demonstrated good to excellent Inter-rater reliability and early construct validity.
These studies present an important starting point to observe and measure the active ingredients within paediatric rehabilitation, incorporating its dynamic nature involving the child and parent within the therapy process.
Keywords: intervention fidelity; family-centred services; paediatric rehabilitation; cerebral palsy; general therapy behaviours; measurement development; Occupational Therapy; Physiotherapy; Occupational Therapy